Textual errors in Serlo of Bayeux’s poem about the capture of Bayeux - Moreed Arbabzadah (Tabularia, 2017)
Current editions of Serlo of Bayeux’s poem about the capture of Bayeux in 1105 contain numerous errors. The most important editions are those of Wright and Brial; I therefore focus on their editions in this article. I provide an example of an error in the Latin text printed by Wright, which probably results from the incorrect interpretation of a gloss. I then turn to Brial’s editions and provide some examples of various types of error in his works. I then discuss errors common to Brial and Wright and propose solutions. Finally, I discuss an unsolved problem.